Exploring Tualang Honey formulation and Synvisc in rabbit osteoarthritis - Abd Rahim, Nour El Huda; Mohamad Amri, Nur Fathonah; Zulkifly, Ahmad Hafiz; Hassan, Habibah; Mohd Jan, Nurul Hafiza; Ibrahim, Mohd Zulfadzli (Malaysian Orthopaedic Association (MOA), 2024)
INTRODUCTION: Tualang Honey, characterised by its anti-inflammatory and antioxidative properties, presents a novel therapeutic approach to osteoarthritis (OA) management. This study evaluates the efficacy of a Tualang Honey Formulation (THF) (Patent no. MY179303-A) injection, compared to Synvisc, a conventional hyaluronic acid injection, utilising radiographic findings in New Zealand White Rabbits (NZWR) as an OA model.